Mr. Crookodile - Bush, John.; Paul, Korky (London : Egmont, 2006)
With a cunning plan to appease his wife, Mr. Crocodile decides to adorn a disguise and rob a bank, but things do not turn out quite like he expects.
2.3
K-3
Keywords: Bank robberies -- Fiction; Crocodiles -- Fiction; Bank robberies -- Fiction; Crocodiles -- Fiction; Readers (Elementary).